2000
DOI: 10.1056/nejm200010053431404
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropathic Postural Tachycardia Syndrome

Abstract: The neuropathic postural tachycardia syndrome results from partial sympathetic denervation, especially in the legs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
265
1
11

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(291 citation statements)
references
References 38 publications
14
265
1
11
Order By: Relevance
“…13 In their assessment of both sympathetic baroreflex sensitivity and cardiovagal baroreflex sensitivity, the function of the autonomic nervous system was intact in the patients, 13 although other researchers have postulated autonomic nervous dysfunction with exaggerated sympathetic nervous activation over compensatory levels while standing as a major mechanism behind the symptoms. 4,5,20,24,27 Elucidation of the pathophysiology of CFS and OI may lead to better therapeutic strategies. Recently, xenon-computed tomography blood-flow studies demonstrated that CFS patients have global cerebral hypoperfusion with reduced absolute cortical blood flow in broad areas, especially in bilateral middle cerebral artery territories, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…13 In their assessment of both sympathetic baroreflex sensitivity and cardiovagal baroreflex sensitivity, the function of the autonomic nervous system was intact in the patients, 13 although other researchers have postulated autonomic nervous dysfunction with exaggerated sympathetic nervous activation over compensatory levels while standing as a major mechanism behind the symptoms. 4,5,20,24,27 Elucidation of the pathophysiology of CFS and OI may lead to better therapeutic strategies. Recently, xenon-computed tomography blood-flow studies demonstrated that CFS patients have global cerebral hypoperfusion with reduced absolute cortical blood flow in broad areas, especially in bilateral middle cerebral artery territories, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of the syndrome is not fully elucidated; however, several lines of evidence suggest abnormalities in sympathetic nervous system function. 1,2 Increased sympathetic nervous system activity has been noted in several prior studies. These observations include high plasma norepinephrine levels, 4 decreased norepinephrine clearance, 5 increased adrenoreceptor sensitivity, 5,6 increased low-frequency/high-frequency ratio of RR-interval variability and low-frequency power of systolic blood pressure (putative measures of sympathetic modulation of RR interval and vascular tone, respectively), 7 and norepinephrine-transporter deficiency.…”
mentioning
confidence: 85%
“…[1][2][3] Symptoms of the disorder include lightheadedness, fatigue, dizziness, palpitations, and nausea. The pathophysiology of the syndrome is not fully elucidated; however, several lines of evidence suggest abnormalities in sympathetic nervous system function.…”
mentioning
confidence: 99%
“…3 Onset of POTS occurs predominantly between the ages of 15 and 50 years, 4 with a female predominance. 1,2,[5][6][7] The female-to-male ratio has been reported to be as high as 5:1. 8 Given the female predominance and the occurrence of POTS during the childbearing years, the effects of this disorder on pregnancy is often raised in clinical practice.…”
Section: © 2010 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%